Just-In-Time Implementation Status Within Libyan Cement Industry (A Case Study) - Rajab Abdullah Hokoma , Hala Mansour Amaigl (Journal of Pure & Applied Sciences, 2018)
This paper investigated the implementation status of Just-In-Time practices within the Libyan cement industry. The required data/information were gathered from the target factories through interviewing the most involved people in the decision making process within this business area, and through a questionnaire, developed for this survey  in order to identify the actual application levels for the key-factors being considered as the most crucial for any successful and effective application. The findings showed that the cement industry suffers from many problems in managerial, manufacturing, and industrial operations. Among of them are lack of clear policies and strategic plans. Based on the findings, the paper recommended that the management body should pay more attention for providing all the requirements to qualify and train the related employees and personnel, providing the spare parts required for maintenance programs, and do not neglect the security aspect, and should focus on the safety issues within the work-place. The paper also suggested that clear policies and strategies should be well-formulated, adapting modern technologies and techniques for maximizing the efficiency and effectiveness throughout the cement industrial operations.